Prenatal diagnosis and family analysis of 17q12 microdeletion syndrome with fetal renal abnormalities - Zhang, Fang; Gu, Qingqing; Song, Jiedong; Zhao, Yali; Wang, Zhiwei; Men, Shuai; Wang, Leilei (Frontiers in Genetics, 2024)
To analyze the prenatal diagnosis, parental verification, and pregnancy outcomes of three fetuses with 17ql2 microdeletion syndrome.We retrospectively reviewed 46 singleton pregnancies with anomalies in the urinary system who underwent amniocentesis from Feb 2022 to Oct 2023 in the Prenatal Diagnosis Center of Lianyungang Maternal and Child Health Hospital. These fetuses were subjected to chromosomal microarray analysis (CMA) and/or trio wholeexome sequencing (Trio-WES). We specifically evaluated these cases' prenatal renal ultrasound findings and clinical characteristics of the affected parents.Results: Three fetuses were diagnosed as 17q12 microdeletions, and the detection rate was 6.5% in fetuses with anomalies in the urinary system (3/46). The heterogeneous deletions range from 1.494 to 1.66 Mb encompassing the complete hepatocyte nuclear factor 1 homeobox B (HNF1B) gene. Fetuses with 17q12 deletion exhibited varied renal phenotypes. Moreover, the clinical phenotypes of the affected parents differed greatly in the two cases (case 2 and case 3) in which the deletion was inherited. For case 3, the mother manifested classic symptoms of 17q12 deletion syndrome as well as unreported characteristics, such as very high myopia.Our findings demonstrate the necessity and significance of offering prenatal genetic testing when various renal anomalies are detected. In addition, our 4 study broadens the phenotypic spectrum of 17q12 deletions. Most importantly, our findings may allow timely supportive genetic counseling and guidance for pregnancy in affected families, e.g. with the help of preimplantation genetic testing (PGT).